miR-25 Regulates Gastric Cancer Cell Growth and Apoptosis by Targeting EGR2 - Yang, Liuqing; Li, Lina; Chang, Pan; Wei, Ming; Chen, Jianting; Zhu, Chaofan; Jia, Jing (Frontiers in Genetics, 2021)
Gastric cancer is one of the most common malignancies, which is harmful to human health. The search for effective drugs or gene therapy has aroused the attention of scientists. So far, microRNAs, as small non-coding RNAs, have the potential to be therapeutic targets for cancer. Herein, we found a highly expressed miR-25 in gastric cancer cell. However, the function of miR-25 for gastric cancer cell growth and apoptosis was unknown. Functionally, we used RT-qPCR, western blot, CCK-8 and flow cytometry to detect gastric cancer cell growth and apoptosis. The results indicated that miR-25 promoted gastric cancer cell growth and inhibited their apoptosis. Mechanistically, we found that a gene EGR2 was a potential target gene of miR-25. Further dual-luciferase results supported this prediction. Moreover, knockdown of EGR2 promoted gastric cancer cell growth and inhibited their apoptosis by flow cytometry detection. Altogether, these findings revealed miR-25 as a regulator of gastric cancer cell growth and apoptosis through targeting EGR2.